Additional risk minimisation measures in the EU– are they eligible for assessment?1. (15th August 2013) - Zomerdijk, Inge M.; Trifirò, Gianluca; Sayed‐Tabatabaei, Fakhredin A.; Sturkenboom, Miriam C. J. M.; Straus, Sabine M. J. M.
ABSTRACT Purpose "Additional" risk minimisation measures (aRMMs) can be necessary to optimise the benefit–risk balance of a drug. Evaluation of effectiveness of these measures has become mandatory with the new European Union (EU) pharmacovigilance legislation in force since July 2012. The aim of this study was to classify the aRMMs in the EU with a special emphasis on the possibilities to analyse the effectiveness of these aRMMs in existing electronic healthcare databases (EHDs). Methods European Public Assessment Reports were reviewed to identify key elements of the aRMMs. Researchers categorised the key elements based on the objectives, i.e. knowledge change or behavioural change and sub‐categorised the behavioural changes. They assessed for each key element if it would be eligible for analysis in existing EHDs. Results 68 drugs with aRMMs contained 801 key elements of which 57% aimed at behavioural changes. 22% of all key elements, all aimed behavioural changes, were assessed eligible for analysis in existing EHDs. These mainly concerned recommendations targeted at healthcare professionals regarding drug prescription, e.g. dose recommendations, contraindications or the need to perform laboratory tests for patient monitoring. Conclusions Only a limited proportion of key elements of the aRMMs could potentially be monitored in existing EHDs as these data sources cannot capture all the required data. Due to difference between existing EHDs, not necessarily all available EHDs are appropriate for every drug or aRMM. To facilitate rapid evaluation of aRMM implementation and timely adjustments, industry and regulatory authorities should agree well‐defined key elements of aRMMs leading to unambiguous actions of the target group. Copyright © 2013 John Wiley & Sons, Ltd.